The effect of conjugated linoleic acid on the growth of weaned piglets - Miran KASTELIC; Drago KOMPAN (Acta Agriculturae Slovenica, 2006)
The effect of conjugated linoleic acid (CLA) on growth parameters of sixteen piglets, divided into two groups was studied. The experiment started when the piglets were 29 days old. Prior the age of 39 days animals were fed restrictively on the same amount of feed, independent of the weight of animal. During the next period of the experiment, between ages of 40 and 75 days, the animals were fed individually, with 1.8 times of maintenance energy. Animals were weighed every week. The experimental group was fed extra with supplement of 1.5% of 80% CLA. The same amount of sunflower oil was used in the control group. During the last period of the experiment, between ages of 76 and 123 days, animals were fed ad libitum with feed without any CLA or sunflower supplement. CLA decreased average feed consumption and weight of the animals. All observed differences were found in the third or last period of the experiment, after the administration of CLA or sunflower oil was finished.